SOCIALIZATION AND ASSISTANCE OF SOCIAL MEDIA UTILIZATION TO INCREASE SELLING POWER OF MSMES IN KERINJING OGAN ILIR VILLAGE - Yusnaini Yusnaini; Burhanuddin Burhanuddin; Arista Hakiki; Nur Khamisah (Universitas Trisakti, 2022)
This community service aims to provide solutions for MSME actors in Kerinjing Village in increasing selling power. To deal with the problems faced by business actors in Kerinjing village, socialization and assistance are needed in introducing, providing understanding and implementing the use of social media to market the products they produce. The implementation of this service is carried out by means of a lecture method related to the material followed by the process of assisting the creation of social media accounts and the use of social media in marketing products. This program of activities has been successfully implemented with satisfactory results. The output from the results of community service to participants is that the product promotion design is more attractive and easier to reach consumers. The results of this activity are expected to become teaching materials that can be delivered to students in the entrepreneurship and accounting information systems course.